A self-adaptive quantum steganography algorithm based on QLSb modification in watermarked quantum image. (24th July 2019) - Qu, Zhiguo; He, Huangxing; Liu, Wenjie; Ma, Songya
As one of important research branches of quantum information hiding, quantum steganography embeds secret information into quantum images for covert communication by integrating quantum secure communication technology and classical steganography. In this paper, based on the novel enhanced quantum representation (NEQR), a novel quantum steganography algorithm is proposed to transfer secret information by virtue of quantum watermarked image. In order to achieve this goal, the least significant qubit (LSQb) of quantum carrier image is replaced with the secret information by implementing quantum circuit. Compared with the previous quantum steganography algorithms, the communicating parties can recover the secret information tampered, meanwhile the tampers can be located effectively. In the experiment result, the peak signal-to-noise ratios (PSNRs) are calculated for different quantum watermarked images and quantum watermarks, which demonstrate the imperceptibility of the algorithm is good and the secret information embedded can be recovered by virtue of its self-adaptive mechanism.